Hepatitis B Vaccination Status among Healthcare Workers in a Tertiary Cardiac Centre: A Descriptive Cross-sectional Study - Dangol, Prati Badan; Shrestha, Battu Kumar; Dhungana, Suraksha (Nepalese Heart Journal, 2025)
Background: Healthcare Workers (HCWs) are at increased risk of occupational exposure to the Hepatitis B virus infection, making vaccination crucial for infection prevention. This study aims to assess vaccination coverage and identify factors influencing uptake among HCWs at a tertiary cardiac center. Methods: We conducted a descriptive cross-sectional study at Shahid Gangalal National Heart Centre (SGNHC), involving 479 healthcare workers, including doctors, nurses, paramedical staffs, and support personnel. Data were collected using a structured electronic and paper-based questionnaire, ensuring comprehensive coverage of vaccination history and awareness. Results: Participants had a mean age of 32.79 ± 9.0 years, with 43 (8.98%) males and 436 (91.02%) females. Of the 479 workers, 179 (37.36%) received complete vaccinations, while 215 (44.89%) received incomplete doses, and 85 (17.75%) had no record of vaccination. The primary reason for non-vaccination was a lack of awareness, reported by 58 (12.11%) of participants; knowledge of the required doses of the vaccination series was 74.11% and 19.62%, respectively Conclusion: In conclusion, the vaccination coverage among healthcare workers at this tertiary cardiac center is low, primarily attributable to inadequate knowledge and awareness. Institutional policies mandating HBV vaccination and education initiatives are recommended.